Bentonite surface modification and characterization for high selective phosphate adsorption from aqueous media and its application for wastewater treatments - S. Yaghoobi-Rahni; B. Rezaei; N. Mirghaffari (Journal of Water Reuse and Desalination, 2017)
Raw and modified bentonite has been used to develop effective sorbents to remove phosphate from aqueous solution. Acid thermoactivation, Rewoquate, Irasoft, calcium, Fe and Al were employed to treat the bentonite. Results show that samples adsorption capacity for phosphate is in the order of, unmodified bentonite = acid thermoactivation < Rewoquate < calcium ≅ Irasoft < Fe < Al ≅ Fe-Al. The phosphate adsorption with Fe-Al-bentonite (FAB) modification was more than 99% and the phosphate removal reached the peak value in the initial 30 min. The phosphate adsorption of FAB was pH independent in the range of 2–10. The common coexisting ions in wastewater have no effect on the phosphate adsorption. The phosphate adsorption results were very well fitted in the Freundlich and Langmuir isotherm model and the maximum adsorption capacity was 8.33 mg P/g at pH 6.5 for 1 hour, which was better than similar modified bentonite with low time and Fe-Al consumption. FAB was characterized by scanning electron microscopy, X-ray diffraction, X-ray fluorescence and Fourier transform infrared. Therefore, the results confirm that FAB is a selective phosphate sorbent and environmentally friendly for its potential application for phosphate removal from wastewater.